Pharmaco-epidemiological aspects of arterial hypertension management in Tomsk Region - E. Yu. Turkasova; T. G. Volkova; T. N. Ketova; E. M. Idrisova; O. S. Kobyakova; S. A. Banin; M. F. Chinyaev (Кардиоваскулярная терапия и профилактика, 2005)
Aim. To investigate real-word antihypertensive drug therapy in Tomsk City and Region. Material and methods. In January-June 2004, non-organized population of Tomsk City and Region was examined, according to the Regional Program «Arterial Hypertension Prevention and Treatment in Tomsk Region, 2004-2008». The examination included anthropometry, blood pressure measurement, and questionnaire survey. In total, 943 people aged 15-89 (472 in the region, 471 – in the city) were examined. Results. In Tomsk City and Region, 39.4% of adult population suffered from arterial hypertension (AH). Among AH patients, 78.7% received various antihypertensive agents: one drug – 44.4%; two drugs – 36.5%; three drugs or more – 19.1%. The most frequently prescribed agents, as monotherapy or a part of combined therapy, were diuretics (47.8%) and ACE inhibitors (46.2%). Conclusion. AH prevalence in Tomsk Region is similar to that in Russian general population. Real-world use of antihypertensive agents does not conflict with the latest recommendations of the Society of Cardiology of the Russian Federation. The patients must be informed more actively about the need for regular, doctor-controlled intake of antihypertensive medications. Various educational programs for hypertensive patients should be developed and implemented.